Transcellular transport of cobalamin in aortic endothelial cells. Issue 10 (9th May 2018) - Hannibal, Luciana; Bolisetty, Keerthana; Axhemi, Armend; DiBello, Patricia M.; Quadros, Edward V.; Fedosov, Sergey; Jacobsen, Donald W.
ABSTRACT: Cobalamin [Cbl (or B12 )] deficiency causes megaloblastic anemia and a variety of neuropathies. However, homeostatic mechanisms of cyanocobalamin (CNCbl) and other Cbls by vascular endothelial cells are poorly understood. Herein, we describe our investigation into whether cultured bovine aortic endothelial cells (BAECs) perform transcytosis of B12, namely, the complex formed between serum transcobalamin and B12, designated as holo‐ transcobalamin (holo‐TC). We show that cultured BAECs endocytose [ 57 Co]‐CNCbl‐TC (source material) via the CD320 receptor. The bound Cbl is transported across the cell both via exocytosis in its free form, [ 57 Co]‐CNCbl, and via transcytosis as [ 57 Co]‐CNCbl‐TC. Transcellular mobilization of Cbl occurred in a bidirectional manner. A portion of the endocytosed [ 57 Co]‐CNCbl was enzymatically processed by methylmalonic aciduria combined with homocystinuria type C (cblC) with subsequent formation of hydroxocobalamin, methylcobalamin, and adenosylcobalamin, which were also transported across the cell in a bidirectional manner. This demonstrates that transport mechanisms for Cbl in vascular endothelial cells do not discriminate between various β‐axial ligands of the vitamin. Competition studies with apoprotein‐ and holo‐TC and holo‐intrinsic factor showed that only holo‐TC was effective at inhibiting transcellular transport of Cbl. Incubation of BAECs with a blocking antibody against the extracellular domain of the CD320 receptor inhibited uptake and transcytosis by 40%. This study reveals that endothelial cells recycle uncommitted intracellular Cbl for downstream usage by other cell types and suggests that the endothelium is self‐sufficient for the specific acquisition and subsequent distribution of circulating B12 via the CD320 receptor. We posit that the endothelial lining of the vasculature is an essential component for the maintenance of serum‐ tissue homeostasis of B12 .—Hannibal, L., Bolisetty, K., Axhemi, A., DiBello, P. M., Quadros, E. V., Fedosov, S., Jacobsen, D. W. Transcellular transport of cobalamin in aortic endothelial cells. FASEB J. 32, 5506–5519 (2018). www.fasebj.org